The monster and puppet show! - Micucci, Kate; Willems, Mo (Elephant & Piggie like reading!, 2026)
"When Monster meets Puppet, they decide to put on a show. Puppet knows what Monster should do! Monster should tell a joke! Monster should dance! Monster should sing! But the more Monster does, the more Puppet wants MORE. What should Monster do when The Monster and Puppet Show! is not fun any ... MORE!?!"--Provided by publisher.